2014
DOI: 10.1645/13-490.1
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem Sporulation ofCeratomyxa shasta(Myxozoa) After Death in Adult Chinook Salmon

Abstract: Ceratomyxa shasta (Myxozoa) is a common gastrointestinal pathogen of salmonid fishes in the Pacific Northwest of the United States. We have been investigating this parasite in adult Chinook salmon ( Oncorhynchus tshawytscha ) in the Willamette River, Oregon. In prior work, we observed differences in the pattern of development of C. shasta in adult salmon compared to juvenile salmon. Adult salmon consistently had large numbers of prespore stages in many of the fish that survived to spawn in the fall. However, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…These data indicated that myxospores were found primarily in carcasses from adult salmon that had senesced and died days after spawning. It is possible that the pansporocyst stage (presporogonic) responds to changes in the microenvironment associated with decomposing tissue (e.g., lytic enzymes, oxygen and pH changes) to complete sporogenesis (see also Kent et al 2014). Myxospore increase in fish carcasses postmortem has also been observed in another Pacific Northwest river, the Williamette River (Kent et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…These data indicated that myxospores were found primarily in carcasses from adult salmon that had senesced and died days after spawning. It is possible that the pansporocyst stage (presporogonic) responds to changes in the microenvironment associated with decomposing tissue (e.g., lytic enzymes, oxygen and pH changes) to complete sporogenesis (see also Kent et al 2014). Myxospore increase in fish carcasses postmortem has also been observed in another Pacific Northwest river, the Williamette River (Kent et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Disease severity is directly related to temperature and may culminate in death, which can occur as early as 15 days post-exposure in fish held at 15°C (Ray et al ., 2012). Myxospores typically mature during terminal stages of infection with the majority released when fish die (although there is a notable exception described below in which spores are shed from apparently healthy fish), possibly triggered by factors produced as tissues become necrotic (Kent et al ., 2014).…”
Section: Ceratonova Shasta Life Cycle and Developmentmentioning
confidence: 99%
“…Chinook and coho salmon are semelparous, dying after they return to freshwater to spawn. Infections in adult salmon by both genotypes I and II are characterized by release of spores only upon the death of the fish, and the process of sporulation continues post-mortem in adult Chinook salmon (Kent et al ., 2014; Foott et al ., 2016). This provides explanation for earlier studies on the effects of C. shasta on pre-spawn mortality where fish that were killed for egg taking had a much lower apparent infection prevalence (18% myxospore positive) compared to fish that died prior to spawning (65% myxospore positive) (Chapman, 1986).…”
Section: Parasite Factors Driving Diseasementioning
confidence: 99%
“…Developmental strategies of C. shasta differ between infections in adult and juvenile salmonid hosts; in adults, release of myxospores occurs after death ( i.e. , post-spawn), while in smolts and parr the parasite is released shortly after infection ( Kent et al, 2014 ). The parasite released from infected adult carcasses is dispersed downriver where deposition overlaps with habitat for the invertebrate host.…”
Section: Introductionmentioning
confidence: 99%